Issues and challenges in online learning: A case study in Malaysia - Maksom, Zulisman; Shahbodin, Faaizah; Che Ku Mohd, Che Ku Nuraini; Al-Fatta, Hanif; Chandini, Ulka; Mohd Kasim, Helmi (Little Lion Scientific Islamabad Pakistan, 2024)
This paper focused on exploring the secondary school teachers’ perceptions toward online learning program which developed during COVID-19 pandemic in Malaysia. To evaluate teachers’ perceptions of teaching and learning engagement, a quantitative survey was conducted. Therefore, teachers’ understanding of teaching and the relation to their engagement in learning are explored in this survey. Hence, there are factors which determined the success of implementing online learning in Malaysia during COVID-19 pandemic such as the readiness of technology which in line with the national humanist curriculum, support and collaboration from all stakeholders including government, teachers, parents, schools, and community. The findings in this paper highlight the teachers’ good sense of teaching and strong correlations between teachers’ perceptions and students’ engagement are significantly influence the online teaching and learning process. Teachers are also suggested to apply more appropriate types of learning tools during classes and pay attention to the nature of the student. The results may assist in advocating for a paradigm shift in online education. The research underscores the need for innovative approaches that leverage the power of technology to inspire online learners and educators thereby contributing to the ongoing improvement of online education.